1994
DOI: 10.1046/j.1420-9101.1994.7020201.x
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of the cyanogenic polymorphism in Trifolium repens L.

Abstract: Trifolium repens L. and Trifolium nigrescens Viv. are two of the approximately six cyanogenic species known in the genus Trifolium.The two species are closely related: T. nigrescens is considered to be one of the diploid ancestors of the amphidiploid T. repens. We studied morphology, meiosis and the cyanogenic system in T. repens (amphidiploid), T. nigrescens (diploid) and their reciprocal hybrids. A comparison of the enzyme linamarase in the species and hybrids shows that there is a general resemblance betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
10
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 2 publications
4
10
1
Order By: Relevance
“…However, this hypothesis is contrary to the results reported by Kakes and Hakvoort (1994) and Kakes and Chardonnens (2000) that T. occidentale did not donate the Li allele to T. repens. Furthermore, the work of Williams (1987) showed that chromosomes in the pollen mother cells of T. repens pair in bivalents at prophase-I of meiosis, which is indicative of an allopolyploid origin.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…However, this hypothesis is contrary to the results reported by Kakes and Hakvoort (1994) and Kakes and Chardonnens (2000) that T. occidentale did not donate the Li allele to T. repens. Furthermore, the work of Williams (1987) showed that chromosomes in the pollen mother cells of T. repens pair in bivalents at prophase-I of meiosis, which is indicative of an allopolyploid origin.…”
Section: Discussioncontrasting
confidence: 94%
“…More recently Kakes and Chardonnens (2000) found that the distribution of cyanotypes in T. repens and T. occidentale are dissimilar, regulated by different mechanisms. These findings lend support to the view of Kakes and Hakvoort (1994) that T. occidentale did not donate active Li alleles to T. repens. Recent studies (Ansari et al 1999) on the molecular organization of 5S and 18S-26S rDNA loci in T. repens and related species support the allotetraploid origin of T. repens, and T. nigrescens subsp.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of the present study on the Zdh enzyme strongly support the theory of disomic inheritance ( BREWBAKER and KEIM 1953;GIBSON and BEINHART 1969;MICHAELSON-YEATES 1986;KAKES and HAKVOORT 1994). The isoloci studied furthermore behave in a Mendelian fashion, ascertaining that the two alleles observed here are allozymes.…”
Section: Discussionsupporting
confidence: 87%
“…T. occidentale has been suggested as the other diploid species (BREWBAKER and KEIM 1953;HOVIN 1962). This origin of T. repens is also supported by a recent study of the cyanogenic polymorphism in the species ( KAKES and HAKVOORT 1994). Some authors, however, suggest that T .…”
mentioning
confidence: 86%